Rancang Bangun Aplikasi Penilaian Kinerja Pegawai Berdasarkan Kompetensi Dengan Metode 360 Degree Pada PDAM Surabaya - Hermawan, Andry; Sunarto, Dewiyani; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: PDAM Surabaya is a company engaged in the field of public service. The company has a Kelola SDM, one of the tasks is to manage human resources and organizational development, especially the development of the organization, which will be carried out by a performance assessment to determine the level of productivity of an employee each year. In order to assess the performance of employees, Organization and Human Resources Development Section felt that such valuation is way less optimal and objective because of the persistence of assessor subjectivity in assessing employee performance. The current performance of appraisal process there is a problem of how to assess employee performance in accordance with objective reality. To assess the performance objectively, PDAM Surabaya need a performance appraisal system that can reduce the number of assessor subjectivity by using 360 Degree and using the competency reference as a guideline for the assessment. Application of performance assessment on PDAM Surabaya employees that have been made will be expected to reduce the subjectivity of the assessor in assessing the employee performance. The report can be taken into consideration and as an input for organizational and human resource development manager in reward for employees which have excellent performance.